Assessment of the 2006 Abuja Fertilizer Declaration With Emphasis on Nitrogen Use Efficiency to Reduce Yield Gaps in Maize Production - Winnie, Ntinyari; Giweta, Mekonnen; Gweyi-Onyango, Joseph; Mochoge, Benson; Mutegi, James; Nziguheba, Generose; Masso, Cargele (Frontiers in Sustainable Food Systems, 2022)
The increased application of nitrogen (N) inputs beyond the current practice is highly recommended for Sub-Saharan Africa to achieve food sufficiency and improve soil fertility. However, the current recommended rates of N fertilizer have not been evaluated for specific crops on their potential to reduce the yield gap and optimize Nitrogen Use Efficiency (NUE) over time. In this study, four N use scenarios were evaluated under field conditions for maize crops in two catchments of the Lake Victoria basin. The scenarios included Business as Usual (BAU, 0 kg N ha-1), 25 % of the Abuja declaration (ADS 12.5 kg N ha-1), 50% of the Abuja declaration (ADS 25 kg N ha-1), and Abuja declaration-Abuja scenario (AS, 50 kg N ha-1). The results revealed that increasing N input levels significantly influenced the growth and yield of maize crops. The AS scenario recorded the highest grain yield increase (167.39 %) in Nyando and 103.25 % in Rangwe catchments compared to the BAU scenario. N deficits were observed in all the N use scenarios with a range of -66.6 to -125.7 kg N ha-1 in Nyando and -62.5 to -105.4 kg N ha-1 in Rangwe catchments with 50 % ADS scenario having the highest deficits. The deficits imply that the added N input is insufficient to create a N balance for optimal NUE with consequent high risks of soil N mining. In both catchments, all N use scenarios were within the recommended APEN level of between 40-60 kg kg-1 N. The partial N balance obtained at Nyando (1.56- 3.11) and Rangwe (1.10- 4.64) were higher than the optimal values, a sign of insufficient of N inputs and possible risk of soil N depletion in all the scenarios. Our findings conclude that the proposed N rates in the region are still very low for food sufficiency and optimized NUE. Therefore, there is a need to explore other sources of N like biological N fixation and organic manure, and inform policy makers to recommend higher rates beyond the “Abuja Declaration” in order to reach target yield and optimizing NUE values based on specific crop recommendations.